Прийоми реконструкції як засіб покращення функціонально-типологічних та об’ємно-просторових рішень типових житлових будинків - Новосад, Ірина Геннадіївна; Novosad, Iryna (КНУБА, 2020)
У статті висвітлюється аналіз забудови міста Києва, автором доводиться, що забудова районів нашого міста, переважно формується з типових житлових будинків, що були побудовані 1955-1990 роки. На сьогоднішній день типовий житловий фонд використав свій термін експлуатації і має багато недоліків у функціонально-типологічному та об’ємно- просторовому рішеннях і потребують проведення реконструкції. Реконструкція дає можливість створити сучасне комфортне житло, що буде відповідати потребам різних верств населення, а також покращить об’ємно-просторові рішення житлової забудови. Також у статті висвітлюються прийоми, та наводяться приклади їх використання при поведені реконструкції. The article analyzes the development of Kiev, from the analysis we see that the development of our city is formed from typical residential buildings built in 19551990. Typical residential houses have five main stages of their development. Each stage has contributed to the development of a constructive and planning solution for a residential building. Temporary indicators require new indicators of comfort. Typical residential buildings have several disadvantages. The layout of the apartment does not meet the requirements of the disabled, the lack of space for functional typological areas, such as a place for a washing machine, dressing rooms. Entrance groups of typical houses are not adapted for the mobility of persons with disabilities, there is no place for a stroller and no place for a concierge. Structures, communications and facades are in poor condition. The negative qualities of a residential building lead to the need for reconstruction. During the reconstruction, it is necessary to take into account the urban planning situation, the structural bearing system of the building, and the requirements of the population. The main requirement for housing, which determines the quality of comfort, is the conformity of the functional-typological zones to the requirements of a particular person, there should also be free space in the house, the facade decoration should be energy-saving. There are a number of techniques, namely: redevelopment within the existing structural system, the extension and superstructure of additional spaces, the organization of landscaping on the roof. Each of the techniques introduces additional positive qualities both in the planning decision and the facade composition, as well as the techniques make it possible to choose the direction in the reconstruction and improve the quality of typical residential buildings of 1955-1990.
Reconstruction techniques for increasing functional-typological and spatial solutions of typical residential buildings.
Приемы реконструкции как метод повышения функционально- типологических и объемно-пространственных решений типовых жилых домов
Keywords: об’ємно-просторові рішення; реконструкція; прийоми; фронтальна композиція; якість житла; функціонально-типологічні рішення; містобудівна ситуація; модернізація; reconstruction; spatial and spatial solutions; functional-typological solution; frontal composition; techniques; quality of housing; modernization; urban planning situation.